Campus shuttle experience and mobility concerns among students with disability in the University of Cape Coast, Ghana. Issue 2 (11th September 2020) - Odame, Prince Kwame; Abane, Albert; Amenumey, Edem Kwesi
Abstract : Although Ghana's Persons with Disability Act 715 calls for the provision of an accessible environment, attention paid to the mobility needs of persons with disability has focused on their access to public facilities like libraries and schools without paying attention to the transport environment connecting the homes of commuters to these public facilities. This study was carried out to examine the road transport infrastructure and mobility needs of students with disability at the University of Cape Coast. Participants consisted of 31 people with visual impairment and one wheelchair user who were engaged through snowballing. Also, the Transport Officer and selected shuttle operators were engaged to ascertain transport support services to students. These were reached through purposive and convenient sampling, respectively. Findings from the study indicate that hostile reception from shuttle operators and the absence of disability‐friendly accessories on campus shuttles constitute a major barrier to participants' use of campus shuttles. The study recommends documentation and enforcement of the free shuttle services for students with disability as well as the modification of existing transport facilities. Abstract : Map of the University of Cape Coast showing campus shuttle route.